Antimicrobial Resistance Development In Vitro: Adaptive Laboratory Evolution Method (Review) - K. E. Borovkova (Регуляторные исследования и экспертиза лекарственных средств, 2025)
INTRODUCTION. High rates of emergence and spread of antimicrobial resistance (AMR) necessitate the rapid development of novel antibacterial medicinal products. The assessment of the microbial potential for AMR development under controlled conditions in vitro can save resources during drug development and marketing authorisation and contribute to creating the most effective medicinal products.AIM. The aim was to determine the possibility of using the adaptive laboratory evolution (ALE) method to study the development of antimicrobial resistance.DISCUSSION. A variety of methods can be used to investigate the mechanisms of AMR and the influence of medicinal products on the evolution of bacteria towards AMR. One of the options is the ALE method. ALE experiments are conducted under controlled conditions with prolonged exposure of microorganisms to an antibacterial agent. ALE experiments can include serial transfers of microorganisms to fresh liquid media or Petri dishes, as well as continuous cultivation of microorganisms in a chemostat. ALE protocols are used to develop resistance to different antibacterial agents and require meticulous control of the experimental conditions. To obtain reliable results in an experiment, it is necessary to identify parameters that may affect AMR development in microorganisms. These parameters include but are not limited to the concentration of the antibacterial agent, the number of consecutive passages, and the duration of incubation.CONCLUSIONS. To achieve the necessary conditions for resistant microorganisms to form, it is essential to adhere strictly to ALE setup requirements, such as using antibacterial agents at subinhibitory or dynamically increasing concentrations (relative to the minimum inhibitory concentrations for the ancestral strain), performing a certain number of passages for ≥20 generations, and incubating cultures until the stationary phase. Despite the fact that ALE experiments are rather lengthy, these studies can reduce the potential waste of resources on developing new compounds that may have to be discontinued at the stage of production because of AMR development.